Evolution of HCV patient characteristics and DAA regimens in the German Hepatitis C Registry (DHC-R) in 2014 and 2015 = Evolution der Charakteristika der HCV Patienten und der DAA Regime im Deutschen Hepatitis C Register (DHC-R) in den Jahren 2014 und 2015 - Sarrazin, Christoph; Buggisch, Peter; Pathil-Warth, Anita (Zeitschrift für Gastroenterologie, 2019)
Background The urgent need in HCV-infected patients with liver disease mandated the rapid implementation of IFN-free DAA combination therapies following their regulatory approval in 2014 and 2015 without full knowledge of the optimal combinations and regimens. Investigating the evolution of the DAA utilization patterns and treatment outcomes could provide learnings for future situations. Methods This was an analysis of a prospective observational database from the German Hepatitis C Registry (DHC-R) covering a period from May 2014 to September 2015. Adult patients had evidence of chronic HCV GT1 or GT4 infection and were treated with an IFN-free combination regimen of simeprevir (SMV) + sofosbuvir (SOF) or other IFN-free regimens: daclatasvir + sofosbuvir (DCV + SOF), ledipasvir/sofosbuvir (SOF/LDV), paritaprevir/r + ombitasvir ± dasabuvir (PrOD), with or without ribavirine (R). Results A total of 5496 subjects were followed during the period. During this period, clinical recommendations and treatment patterns evolved rapidly in response to new evidence from clinical trials and clinical routine and regulatory approval of additional regimens. High SVR12 rates were seen in this cohort, even in hard-to-treat patient subgroups. In the multivariate analysis, gender, age, advanced cirrhosis, and intensified treatment for cirrhotics were associated with treatment outcome. Conclusion Despite limited knowledge of the optimal utilization of the newly approved DAA combinations and treatment durations as well as their comparative efficacy and safety profiles, high SVR rates were achieved regardless of the DAA combination. These outcomes were facilitated by the rapid adaptation of clinical recommendations. Future situations with high unmet medical need may follow a similar approach.